2002
DOI: 10.1046/j.1365-2036.2002.01298.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral beclometasone dipropionate in the treatment of active ulcerative colitis: a double‐blind placebo‐controlled study

Abstract: SUMMARYAim: To evaluate efficacy and safety of oral beclometasone dipropionate (BDP) when added to 5-ASA in the treatment of patients with active ulcerative colitis. Methods: In a 4-week, placebo-controlled, double-blind study, patients with extensive or left-sided mild to moderate active ulcerative colitis were randomized to receive oral 5-ASA (3.2 g ⁄ day) plus BDP (5 mg ⁄ day) or placebo. Clinical, endoscopic and histologic features, and haematochemical parameters were recorded at baseline and at the end of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 19 publications
1
90
0
Order By: Relevance
“…Patients with the DAI score <3 are considered in clinical remission, 3-6 in mild, 7-10 in moderate and >10 in severe activity of the disease. 24 Exclusion criteria were:…”
Section: Patientsmentioning
confidence: 99%
“…Patients with the DAI score <3 are considered in clinical remission, 3-6 in mild, 7-10 in moderate and >10 in severe activity of the disease. 24 Exclusion criteria were:…”
Section: Patientsmentioning
confidence: 99%
“…In previous studies, the role of rectal formulation of BDP in treatment of UC has been evaluated in comparison with 5-ASA or prednisolone sodium phosphate enemas showing similar efficacy for mild or moderate distal disease. [8][9][10][11][12][13][14][15][16][17][18] A standard dose of BDP 5 mg od (1 tablet day) has been established in the study conducted by Rizzello et al 9 In this study, administration of 5 mg or 10 mg daily showed therapeutic equivalence in patients affected by mild to moderate extensive or left-sided UC, whilst morning plasma cortisol level decreased in the 10 mg group without changes in vital signs. Oral BDP at a standard dose has been studied in treatment of active extensive or left-sided UC, either in combination with 5-ASA or alone resulting effective and safe, without signs of pituitaryadrenal function impairment.…”
Section: Discussionmentioning
confidence: 86%
“…The Campieri et al and Rizzello et al studies found no difference between the 2 medications with similar remission rates; 41,54 however, Rizzello et al found that at 4 weeks, patients treated with beclomethasone achieved clinical remission in 58.9% versus 34.4% of patients treated with the 5 ASA agent. 53 The mean age for these 3 studies was 40.3 years. Based on mean age plus SD, there were no elderly patients in the Rizzello 2001 study, and less than 16% in the other two studies.…”
Section: Efficacy Of Immunosuppressant Agentsmentioning
confidence: 98%
“…[39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58] All 20 studies reported a mean age. The composite mean age was 38.5 years, with a mean range of 30.5 to 46.4 years.…”
Section: Immunosuppressant Age Summationmentioning
confidence: 99%